2019
DOI: 10.1177/1540415319874809
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass of U.S. Hispanics/Latinos From the Hispanic Community Health Study/Study of Latinos (HCHS/SOL): How Do Diet Quality and Sedentary Time Relate?

Abstract: Little evidence exists on diet quality- and sedentary time-related differences in body mass index (BMI) among immigrant and nonimmigrant Hispanics/Latinos with different lengths of U.S. residence. A total of 13,962 (80.2% foreign-born) Hispanic Community Health Study/Study of Latinos (HCHS/SOL) participants aged 18 to 60 from four U.S. cities (Bronx, NY; Chicago, IL; Miami, FL; and San Diego, CA) underwent standardized interviews and fasting blood tests. Diet quality was total Alternative Healthy Eating Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This result may be explained by the inverse relationship between educational, income-status and age-group characteristics. Adolescents cannot be enrolled on any course higher then high-school degree and depend financially on their parents/caregivers and report more time on leisure screen-time and eating more unhealthy food sources (i.e., savory snacks, sweets and candies, and SSB) [31,35]. This result confirms that sedentary behaviors and energy-dense food items are inversely associated.…”
Section: Discussionsupporting
confidence: 52%
“…This result may be explained by the inverse relationship between educational, income-status and age-group characteristics. Adolescents cannot be enrolled on any course higher then high-school degree and depend financially on their parents/caregivers and report more time on leisure screen-time and eating more unhealthy food sources (i.e., savory snacks, sweets and candies, and SSB) [31,35]. This result confirms that sedentary behaviors and energy-dense food items are inversely associated.…”
Section: Discussionsupporting
confidence: 52%
“…Among North American studies with native-born references, risks generally converged to native levels [32,44,102,119,123,128], with some evidence of divergence [34,39,60,123] or unclear patterns relative to natives [39,93,109,114]. European evidence on convergence was more inconclusive, varying by country of origin and destination [64,85,131].…”
Section: Tobacco Usementioning
confidence: 99%
“…With one exception [117], all included tobacco-related studies referred to smoking. In North America, most studies revealed increased risks of smoking with longer residence among general immigrant populations [67,89,96,102,109,128,146], as well as Latino/Hispanic [71,119] and African/Afro-Caribbean [44,127] immigrants specifically. Findings among Asian immigrants ranged from increasing [100,103,117] to decreasing [34,72,78,115] risks, or no trend at all [50,90,133].…”
Section: Tobacco Usementioning
confidence: 99%
See 2 more Smart Citations